Effect of Spacing on Different Short Duration Rice Varieties in T. Aman and Boro Season (Bangladesh Rice Journal, 2025)
The selection of appropriate plant spacing may contribute to the yield potential of a rice variety. This experiment was conducted at the West Byde of BRRI farm, Gazipur during T. Aman’2017 and Boro' 2017-18 seasons to find out the optimum spacing of different short duration rice varieties.  In T. Aman season the treatments were three rice varieties (V1 = BRRI dhan71, V2 = BRRI dhan75 and V3 = BINA dhan17) and five spacings (S1 = 15 cm × 15 cm, S2 = 20 cm × 15 cm, S3 = 20 cm × 20 cm, S4 = 25 cm × 20 cm and S5 = 25 cm × 25 cm). In boro season the treatments were four rice varieties (V1 = BRRI dhan81, V2 = BRRI dhan84, V3 = BRRI dhan86 and V4 = BRRI dhan28) and the spacings were same as T. Aman season.  In each season, the treatments were arranged in a Split-plot design as variety in the main plots and spacing in the sub plots with three replications. In T. Aman season, irrespective of variety and spacing, the number of tillers per hill increased sharply and reached the maximum at 30 to 45 DAT then gradually decreased. BRRI dhan75 gave the highest grain yield which was statistically identical with the yield of BRRI dhan71 and BINA dhan17. The spacing 20 cm × 15 cm gave the highest grain yield compared to other spacing. On the other hand, during Boro season the number of tillers per hill increased sharply and reached the maximum at 60 to 80 DAT then gradually decreased. The 20 cm × 20 cm spacing gave the highest grain yield and among the varieties BRRI dhan84 gave the highest grain yield.Bangladesh Rice J.27(1): 75-83